Big bag: tecnologia a serviço da proteção do patrimônio genético do Brasil - COSTA NETO, Sebastião Rodrigues da (2019)
This work reports the development of a computational information system for the management of BAGs (active germplasm banks) that helps breeders of plants in plant breeding programs, in order to facilitate the management of the information. The system was inspired by the needs and supported in the management techniques of the State University of the Northern Fluminense Darcy Ribeiro of the state of Rio de Janeiro in order to make the manual process of information management more agile and efficient through computational resources and information technologies. The process of documenting and managing the information of active germplasm banks is so important, since in the BAGs, the genetic code has value resulting from its documentation and easy access to its information. Often times, this information is managed inefficiently, through spreadsheets or even in writing, generating difficulties in the processes of consultation, analysis and information management. The final result of the study and development of the application mainly proposes substantial improvements in the documentation procedure of genetic resources as well as in the decision-making process regarding the conservation of these resources, thus assigning qualitative value to the BAGs themselves, generating appropriate documentation and management control higher.